Spatial performance with perspective displays as a function of computer graphics eyepoint elevation and geometric field of view - Barfield, Woodrow; Hendrix, Claudia; Bjorneseth, Ove (Applied ergonomics, 1995)
The purpose of this study was to investigate the effect of varying the elevation of the computer graphics eyepoint and the geometric field of view on judgements of spatial information using a stereoscopic perspective display. Twelve subjects judged the elevation and azimuth angle separating two computer-generated objects viewed using an eyepoint elevation that ranged between −15 ° and 45 ° and a geometric field of view that ranged between 40 ° and 80 °. The results of the study indicated that judgements of elevation were affected by the compression of the vertical axis resulting from the raised eyepoint elevation. Furthermore, azimuth judgements were influenced by both the eyepoint elevation and the geometric field of view. Implications of the results for the design of displays and for spatial performance using stereoscopic displays are discussed.